Child and family health nurses' roles in the care of infants and children: A scoping review. (September 2022) - Wightman, Louise; Hutton, Alison; Grant, Julian
Child and family health nurses (CFHNs) work in a variety of settings with families to promote optimal growth and development in infants and children from birth to 5 years. Literature is available about models of care that CFHNs use in their work, but there is limited information about how CFHNs enact care specifically for infants and children. The aim of this scoping review was to identify and contextualize existing knowledge of how CFHNs, both in Australia and internationally, care for infants and children. Arksey and O'Malley's (2005) framework was used to review 27 studies from Australia, Sweden, Finland, United Kingdom (UK), United States of America (USA), Ireland, Netherlands, Denmark and Canada. It was identified that CFHNs, equipped with a range of assessment tools for early intervention and health promotion, use a partnership approach when working with parents to promote the health and well-being of infants and children. The literature revealed the complexity of the roles undertaken by CFHNs when caring for infants and children. Review findings indicated that CFHNs' work is distinctive because it is conducted in home and community settings, is relational and salutogenic in nature and is also located in the domain of preventative health and early intervention.